RATTAN: THE TEMPTATION OF CONTEMPORARY DESIGN (Innovation in Woodworking Industry and Engineering design, 2026)
Rattan is an exclusively lightweight material with exotic character; it is a symbol of Asiatic countries; of gardens and resort hotels. 20th C designers are tempted by this material that combines well with metals and wood. Rattan itself is imitated with artificial materials, used to knit garden furniture; it is a preferable choice because it is indestructible by atmospheric conditions. Today, great designers are inspired by the formal potential of rattan both as a structural material and as a mesh or woven panels used for the wide surfaces of seating and lying furniture (seats and backrests). They are not limited only in the garden field of application; they use the potential of this material for the dwelling. In this paper, we are going to consider designer works of different periods of the 20th and 21st century, that are influenced by the qualities and specifics of the material rattan; by analyzing and classifying those features that make it so attractive to furniture designers.